The Influence of Christianity on Modern Chinese Education: Insights from the Development of Church Schools - FAN Junming, (Journal of Research for Christianity in China (JRCC), 2025)
Church-affiliated schools originally emerged as a fusion of Western religion and education. After Christianity became the dominant Western religion, it permeated Western educational and theological thought, with church schools establishing a presence both in the West and its colonial territories. This paper specifically examines the phenomenon of church schools prior to the 20th century, analyzing their role in the enlightenment and development of modern Chinese education. First, it discusses Christianity's transformation of modern Chinese education, including foreign language curricula, science education, the proliferation of church-affiliated universities, gender equality education, and religious education. Second, it explores Christianity's influence on the institutional framework of Chinese higher education, such as shifts in university governance paradigms, the introduction of interdisciplinary programs, and the adoption of new institutional systems. In China, missionary schools served not merely as institutions for knowledge transmission. More significantly, through the dissemination and renewal of educational systems, they transformed the traditional academic structures and entrenched mindsets of the Qing Dynasty. Universities proliferated under the missionary school model, disciplinary specialization advanced, and education moved beyond traditional monodisciplinary learning. This diversification of higher education fostered a cohort of Chinese intellectuals capable of competing on the global stage. Christianity and missionary schools thus provided a crucial catalyst for the development of the modern university system.
Keywords: Christianity Modern Chinese Education Church Schools